95.2k views
0 votes
Solve Equation
1. 6 - 4x = 6x - 8x + 2

1 Answer

2 votes

Answer:

X=2

Explanation:

Step 1: Simplify both sides of the equation.

6−4x=6x−8x+2

6+−4x=6x+−8x+2

−4x+6=(6x+−8x)+(2)(Combine Like Terms)

−4x+6=−2x+2

−4x+6=−2x+2

Step 2: Add 2x to both sides.

−4x+6+2x=−2x+2+2x

−2x+6=2

Step 3: Subtract 6 from both sides.

−2x+6−6=2−6

−2x=−4

Step 4: Divide both sides by -2.

−2x/−2=−4/−2

Step 5 :Answer

X=2

LEAVE A LIKE IF THIS BELPED PLEASE.

User Joachim Rohde
by
5.5k points